Tax Revenue, Investment, and Economic Growth in Nigeria: A Systematic Review of Empirical Evidence on Socio-Humanistic Dynamics - Ifeoma Florence Okpalanwabude (MANDAILING GLOBAL EDUKASIA, 2026)
Sustainable economic growth is among the top macroeconomic goals of Nigeria; however, the nation has been witnessing erratic growth rates, low capital formation, and the infrastructural deficits. At the same time, the amount of investment by the private is below the level that can be widely regarded as sufficient to facilitate long-term development. This research utilized systematic review design to analyze empirical evidence of tax revenue, investment and economic growth in Nigeria. Academic databases were searched using predefined keywords to obtain relevant peer-reviewed articles and institutional reports. The inclusion criteria used to select studies focused on the empirical method and relevance to Nigeria. Data extracted underwent a narrative and comparative synthesis to determine patterns, gaps in the methodology and the moderating effects of public and private investment in tax-growth relationship. The systematic review shows that tax revenue by itself does not ensure economic growth, but its success depends mostly on its interaction with the dynamics of public and private investment. In order to attain sustainable economic growth, Nigeria should embark on balanced tax reform, enhance governance in the area of public expenditure and develop enabling environment to spur private investment. A combined fiscal-investment policy is thus needed in long-run development.